The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4172/0974-8369.1000294
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplements Use in Competitive and Non-Competitive Boxer: An Exploratory Study

Abstract: Intensity training, talent, and an adequate diet represent the crucial factors for the success of athletes. Unfortunately, athletes prefer intaking substances to quicker and easier increase their performance compared to traditional training. For this reason there has been a significant spread of enhancing substances drugs and dietary supplements (DS), although, as already broadly evidenced, the abuse of those substances could seriously damage athletes' health. Indeed, DS could contain substances that are not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
(62 reference statements)
0
6
0
2
Order By: Relevance
“…However, gender differences in drug intake depend on several factors: genetics, physiology, anatomy, and sociocultural expectations and experiences (Badoud et al, 2011;Mazzeo, 2016;Santamaria, 2016). Moreover, gender also influences the course and treatment of substance use disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gender differences in drug intake depend on several factors: genetics, physiology, anatomy, and sociocultural expectations and experiences (Badoud et al, 2011;Mazzeo, 2016;Santamaria, 2016). Moreover, gender also influences the course and treatment of substance use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…It was necessary create an independent organization with the sole purpose to defeat the doping in the sport (WADA, 2010;Overbye, Knudsen, & Pfister, 2013). For this reason, in 1999, it was created the World Anti-Doping Agency (WADA), an international organization, with the aim to promote, coordinate, and monitor the fight against doping in sport in all its forms Santamaria, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to Suzic et al, 2011 the athletes who practice individual sport take more dietary supplements than those of collective sports. Mazzeo et al, 2016 showed that boxers take DS for sport and health. They have no awareness of the benefits of supplements and when and which supplements can be used in the event of a sedentary or sporting life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in elite athletes, the misuse and abuse of the abovementioned substances represents a serious health problem, as well as sports lawfulness, because the ergogenic aids can conceal doping substances present in the WADA list and are not always subject to strict controls (Mazzeo, 2016;Mazzeo et al, 2016). In competitive competitions, in fact, the use of any drug substance prohibited by WADA is allowed only for medical reasons and only by virtue of an exemption for therapeutic purposes and therefore documented by the doctor.…”
Section: Discussionmentioning
confidence: 99%
“…The nutrition of the sportsman must ensure the contribution of energy, in the form of calories and promoteand maintain a high level of psychophysical wellbeing (Mazzeo, 2016;Chulvi-Medrano et al, 2019). There are variations in energy expenditure depending on the type of sports activity considered and practiced (Hawley et al, 1995) but also in relation to the registry and morphological variables (Illiano et al 2017;Montesano et al, 2013); it is important to draw up a training protocol with a proper nutritional structure associated, where necessary, with a correct integration of vitamins and / or essential fatty acids (Ashbaugh., McGrew., 2016;Mazzeo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%